Prevalence of cleft lip and palate and associated factors in Brazil's Midwest: a single-center study - FERRARI-PILONI,Carolina (2021)
Abstract: The aim of this study was to evaluate the prevalence of cleft lip and/or palate (CL/P) and associated factors in patients treated at a referral service in Brazil's Midwest. Data were obtained from medical records on file between 2010 and 2017 for this epidemiologic and associational study. A descriptive analysis of the sociodemographic and clinical data was carried out, after which the data were analyzed using the chi-square test and Poisson regression with robust variance. A total of 1,696 medical records were eligible. The requests for rehabilitation were mainly for children in the early years of life, and were mostly for patients from low-income families in the state of Goiás. CL/P was more prevalent in its most severe morphological representation (cleft lip and palate), and the most frequently affected side was the left. Syndromic cleft was present in 4.1% of the cases, and the Pierre Robin sequence and Apert syndrome appeared more frequently. Adjusted multivariate Poisson regression showed an association between cleft palate and the presence of syndromes, since the prevalence was 2.33 times higher in this case than that of no syndrome. Cleft lip and palate were associated with males, whereas cleft palate was associated with females. This study highlights the importance of collecting and analyzing epidemiological data, managing health service planning, and allocating funds to assist cleft patients.